2010
DOI: 10.1111/j.1469-0691.2010.03334.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on antifungal agents for paediatric patients

Abstract: Paediatric age groups display important differences in host biology, predisposing conditions, epidemiology and presentation of fungal infections relative to the adult population. During the past decade, several new antifungal agents have been developed. Although not all of these agents are yet approved for children, the paediatric development of antifungal agents has moved forwards in an exemplary manner. Invasive fungal infections will remain important causes of morbidity and mortality in immunocompromised pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…In a retrospective chart review, it was found that treatment of osseous coccidioidomycosis with amphotericin B was associated with fewer cases of relapse as compared to azole therapy 14 . Lipid formulations of amphotericin B, including amphotericin B colloidal dispersion, amphotericin B lipid complex and liposomal amphotericin B are associated with less renal toxicity and fewer infusion-related side effects than the conventional amphotericin B deoxycholate 93 .…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective chart review, it was found that treatment of osseous coccidioidomycosis with amphotericin B was associated with fewer cases of relapse as compared to azole therapy 14 . Lipid formulations of amphotericin B, including amphotericin B colloidal dispersion, amphotericin B lipid complex and liposomal amphotericin B are associated with less renal toxicity and fewer infusion-related side effects than the conventional amphotericin B deoxycholate 93 .…”
Section: Resultsmentioning
confidence: 99%
“…This antifungal has been recently approved by the Food and Drug Administration and the European Medicine Agency for the treatment of invasive aspergillosis, fusariosis and scedosporiosis [3,4]. It is much more potent against Aspergillus than Anfotericina B, and its greater affinity for the 14ademethylase makes it also more potent than fluconazole [2].…”
Section: Discussionmentioning
confidence: 99%
“…All these amphotericin formulations have been used to treat invasive candidiasis in neonates [2123] despite not having specific guidance for this population on the Food and Drug Administration (FDA) label [24–26]. The European Medicines Agency (EMA) has only approved L-AmB as one of the first-line therapeutic options for the treatment of candidemia and deeply invasive candidiasis [27, 28]. Currently, ABCD manufacturing is suspended [29].…”
Section: Polyenesmentioning
confidence: 99%